Rozwiąż równanie .
a.3x - 2(1 - 2x) = 0,5(3x + 1,5)
b. 3 ⅓ x +8 = 4 ⅖x - 8
c. 2(5a - 3) - a - 4(3a - 2) = 0
d. 2b - (1 - b) = 11- b
e. 2/5 ( x - 2) = x+4
f. ⅖(x - 2) = x+4
g. 3y - 2 (y -1 ) = -6
h. 3(3 - 5y) = 90 - 5 (3y - 2)
¼z + (z - 6) = ⅔(z - 2)

1

Odpowiedzi

Najlepsza Odpowiedź!
2010-04-14T16:34:47+02:00
A.3x - 2(1 - 2x) = 0,5(3x + 1,5)
3x-2+4x=1,5x+0,75
3x+4x-1,5x=0,75+2
5,5x=2,75 |:5,5
x=0,5
b. 3 ⅓ x +8 = 4 ⅖x – 8
3i 1/3x – 4i 2/5x= -8 -8
3i 5/15x – 4i 6/15x=-16
-1i 1/15 x =-16
- 16/15x= -16 |* (-15/16)
x= 15
c. 2(5a - 3) - a - 4(3a - 2) = 0
10a-6 -a -12a +8=0
10a-a-12a= 6-8
-3a=-2 |: (-3)
a= 2/3
d. 2b - (1 - b) = 11- b
2b-1+b=11-b
2b+b+b=11+1
4b=12 |:4
b=3
e. 2/5 ( x - 2) = x+4
2/5 x - 4/5=x+4
2/5x-x=4+ 4/5
-3/5x = 4i 4/5 |*(-5/3)
x= 24/5 * (-5/3)
x= -8
f. ⅖(x - 2) = x+4
2/5 x - 4/5=x+4
2/5x - x= 4+ 4/5
-3/5x = 24/5 |*(-5/3)
x= -8
g. 3y - 2 (y -1 ) = -6
3y-2y+2=-6
y=-6-2
y=-8
h. 3(3 - 5y) = 90 - 5 (3y - 2)
9-15y=90 -15y +10
-15y+15y= 90+10-9
0=/= 91 (= jest przekreslone;)
i. ¼z + (z - 6) = ⅔(z - 2)
1/4 z +z-6 = 2/3 z - 4/3
1/4z+z- 2/3z = -4/3 +6
3/12z+z - 8/12z= - 1 i1/3 + 6
7/12 z = 4 i 2/3
7/12 z = 14/3 |* 12/7
z= 8
1 2 1